2010
DOI: 10.1007/s10461-010-9796-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association of HIV Conspiracy Beliefs with Sexual Risk Among Black Males Living with HIV

Abstract: Research is needed to identify culturally relevant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 16 publications
3
59
0
Order By: Relevance
“…In other words, as cultural mistrust increased, levels of medical mistrust and HIV conspiracy beliefs increased also. This finding is similar to other research that supports the interconnectedness of these variables [10].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In other words, as cultural mistrust increased, levels of medical mistrust and HIV conspiracy beliefs increased also. This finding is similar to other research that supports the interconnectedness of these variables [10].…”
Section: Discussionsupporting
confidence: 93%
“…In a study by Ross et al, a significant correlation was found between African American males' HIV conspiracy theory beliefs and condom use, such that those who held conspiracy beliefs were less likely to use condoms [16]. Similar findings were reported in a longitudinal study by Bogart et al: the presence of HIV conspiracy beliefs was a significant predictor of unprotected intercourse with HIV-positive or unknown sero-status partners [10].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…29 In the same sample, HIV-infected men who endorsed genocidal conspiracy beliefs were also more likely to report unprotected sex. 31 Previous studies have not addressed the degree to which HIV conspiracy beliefs may influence willingness to participate in HIV prevention research in general, and HIV vaccine research in particular. More than 30 years into the HIV/AIDS epidemic, an effective HIV vaccine remains an elusive public health goal.…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional telephone survey of a random sample of African Americans, Bogart and Thorburn (2005) reported that stronger HIV/AIDS conspiracy beliefs were associated with more negative attitudes and less consistent condom use among men; negative attitudes towards condoms partially mediated the relationship between conspiracy beliefs and condom use. Moreover, Bogart and colleagues (Bogart, Wagner, Galvan, & Banks, 2010;Bogart, Galvan, Wagner, & Klein, 2010) have found that HIV-positive African American men have relatively high levels of conspiracy beliefs -with almost two-thirds of their sample endorsing at least one HIV conspiracy belief and almost half endorsing at least two beliefs. They found that endorsement of HIV conspiracy beliefs, particularly treatment-related beliefs (e.g., antiretroviral medication causes AIDS), were related to lower likelihood of optimal treatment adherence and a higher likelihood of unprotected intercourse.…”
Section: Introductionmentioning
confidence: 99%